ECMO without anticoagulation in patients with disease‐related severe thrombocytopenia: Feasible but futile?. Issue 11 (15th July 2019) - Hermann, Alexander; Schellongowski, Peter; Bojic, Andja; Robak, Oliver; Buchtele, Nina; Staudinger, Thomas
Abstract: Severe thrombocytopenia poses a high risk for bleeding thus representing a relative contraindication for anticoagulation and therefore extracorporeal membrane oxygenation (ECMO). We herein report on a series of immunocompromised patients with severe thrombocytopenia undergoing long‐term ECMO without systemic anticoagulation. We retrospectively identified seven adult patients with anticoagulation withdrawal for ≥3 days (range 5–317) during venovenous ECMO therapy due to thrombocytopenia < 50 G/L treated in a university‐affiliated hospital from January 2013 to April 2017. All ECMO systems used were heparin coated. Overall, 530 ECMO days were observed, 404 (76%) of them without systemic anticoagulation. Platelet count during ECMO treatment was 24 G/L (median, range 1‐138), ECMO duration was 35 days (5‐317), and ECMO was run without any anticoagulation for 20 days (5‐317). Altogether, five clotting events were seen leading to oxygenator exchanges. Bleeding was common including one fatal intracerebral hemorrhage. Altogether, 29 platelet concentrates per patient (7‐207) were administered, which correspond to 0.8 per day (0.6‐1.3). One patient survived ICU and hospital. In patients with thrombocytopenia, ECMO can be run without anticoagulation even for considerably long periods of time. Bleeding remains common, while clotting events seem to be rare. However, prognosis of this patient population undergoing ECMO support seems grim.